Comparative Study of Learning Motivation Between Students Who Live in the City and Within the City of Bagan Siapi-Api at SMA Negeri 1 Bangko - Wiwit Safitri; Jumili Jumili; Supentri Supentri (CV. Rayyan Dwi Bharata, 2023)
This research has a background, namely the phenomenon arises based on pre-research that has been carried out by previous researchers and in accordance with field conditions which shows that there is a comparison of learning motivation between students who live in the city and outside the city of Bagan Siapiapi at SMA Negeri 1 Bangko which is characterized by students who are often late to school, students who often don't do homework, are lazy when working on questions given by the teacher in class. This research wants to know what are the learning motives of students who live in Bagan Siapi-api city and outside the city at SMA Negeri 1 Bangkok. The purpose of this research is to help increase knowledge and understanding of students' learning motivation at school. In this study, there was a population of all students of SMA N 1 Bangko consisting of 380 students. The sample in this study was 57 students using the proportional sampling method. Data collection methods include questionnaires, observations, question and answer, and documentation. In this study the data analysis technique used was descriptive statistics and used the T-Test analysis with the help of SPSS. Based on findings from studies comparing students' motivation to learn. The hypothesis is that students of SMA N 1 Bangko who live outside the city and outside the city of Bagan Siapi-api have learning motivation that is not significantly different and can be accepted and controlled for.